A Comparison Between Predicted And Actual Performances Of An Embankment Built Over A Stone Column Area - Ridha, Ahmed Dhya’a M. (2013)
In stone column experiences, actual settlements, consolidation times, and other performance indicators often disagree with the predicted ones. In this study, measurements particularly on actual settlements and consolidation times were made on an embankment built over stone columns. The area of study, situated at Kodiang, Kedah, as a part of the electrified double track project between Ipoh to Padang Besar, consisted of Zone 1 and Zone 2. The embankment over Zone 1 was 4 m thick, while that of Zone 2 was 2 m thick. The underlying soil material was marine clay of northern region of Peninsular Malaysia. The consolidation time allowed for embankments in the project was 45 days after achieving top surcharge levels. The rapid gain in bearing capacity of the treated soil and embankment stability achieved due to the improved soil were also assessed. Other behaviors noted were change in pore pressures and lateral displacements of soil under loads. Extensive soil investigation and instrumentation have been carried out in the study particularly to compare between actual and predicted behavior of the embankments. It was found that actual field settlements were generally lesser than predicted.